TOWARDS THE USE OF SOLAR BEAM CONCENTRATORS AS AN ALTERNATIVE ENERGY SOURCE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The main idea of the article is to expand the functionality of magnifying glasses, and magnifying glasses act as an alternative source of energy. Using a magnifying glass to heat water will give a lot in the field of saving electrical energy.
Keywords: magnifier, renewable energy, ariston, water heating, magnifying glass function expansion.